Depletion of Highly Abundant Proteins in Blood Plasma by Ammonium Sulfate Precipitation for 2d-Page Analysis - Mahn-Osses, A (2011)
Ammonium sulfate precipitation (ASP) was explored as a method for depleting some highly abundant proteins from blood plasma, in order to reduce the dynamic range of protein concentration and to improve the detection of low abundance proteins by 2D-PAGE. 40% ammonium sulfate saturation was chosen since it allowed depleting 39% albumin and 82% ?-1-antitrypsin. ASP-depletion showed high reproducibility in 2D-PAGE analysis (4.2% variation in relative abundance of albumin), similar to that offered by commercial affinity-depletion columns. Besides, it allowed detecting 59 spots per gel, very close to the number of spots detected in immuno-affinity-depleted plasma. Thus, ASP at 40% saturation is a reliable depletion method that may help in proteomic analysis of blood plasma. Finally, ASP-depletion seems to be complementary to hydrophobic interaction chromatography (HIC)-depletion, and therefore an ASP-step followed by a HIC-step could probably deplete the most highly abundant plasma proteins, thus improving the detection of low abundance proteins by 2D-PAGE. © 2011 Elsevier B.V.